Evaluation of the antioxidant activity to the nanoprepared propyl gal-late. - Ibraheem, Mais; Murshidy, Zahraa; Al-Ghanimi, Ali (Journal of Kerbala for Agricultural Sciences, 2017)
A nanohybrid compound PG-ZnO was prepared using sol-gel ion exchange method between the antioxidant propyl gallate and zinc oxide . The new nanoantioxidant compound was identified. FT-IR spectroscopy revealed the appearance of new groups in the PG-ZnO spectrum which indicates the formation of new antioxidant . The X-Ray Diffraction (XRD) spectrum revealed the appearance of new diffraction planes in the PG-ZnO spectrum in compare with the spectrum of zinc oxide . The antioxidant activity of PG-ZnO was studied using free radical scavenging method. Result revealed that IC50 were (75 and 25) µg/ml for the nano and free antioxidant , respectively.